Intrauterine infusion of autologous platelet-rich plasma modulates endometrial immune status and improves pregnancy outcomes in patients with persistent chronic endometritis - Chen, Xian; Chen, Mingye; Liu, Meng; Qi, Lingbin; Liu, Zhiqiang; Chen, Cong; Liang, Binfa; Yang, Xiaobing; Zhang, Tao; Li, Yuye; Lian, Ruochun (Frontiers in Immunology, 2025)
BackgroundChronic endometritis (CE) has been widely recognized as a potential cause of infertility, however, access to effective treatment is a formidable challenge due to the rudimentary understanding of the pathogenesis of persistent CE. Here, we aimed to analyze the impact of platelet-rich plasma (PRP) treatment on pregnancy outcomes and the endometrial microenvironment in patients with persistent CE.MethodsA total of 89 infertility patients were selected, including 56 non-CE (as the control group) and 33 persistent CE. The persistent CE patients received an intrauterine infusion of PRP four times before embryo transfer. Immunohistochemistry staining and transcriptomic sequencing were used to investigate the uterine-specific role of PRP in patients with persistent CE.ResultsThe implantation rate and clinical pregnancy rate were significantly increased in the cured CE group compared to the non-cured CE group. After PRP treatment, the proportions of endometrial CD8+ T cells, CD56+ NK cells, Foxp3+ Treg cells, and T-bet+ Th1 cells were significantly decreased in patients with persistent CE. Specifically, DEG analysis showed that genes implicated in endometrial receptivity-related and antimicrobial were upregulated and genes involved in the immune response processes were downregulated in cured CE patients after PRP treatment. Functional enrichment analysis suggested that the effects of changes in leukocyte chemotaxis-related genes played a critical role in the endometrial immune environment.ConclusionsAutologous PRP treatment has been shown as a potentially successful therapy for improving pregnancy outcomes by reconstructing the uterine local immune microenvironment to improve endometrial receptivity in patients with persistent CE.